Protective Role of Cepharanthine Against Equid Herpesvirus Type 8 Through AMPK and Nrf2/HO-1 Pathway Activation - Shuwen Li; Liangliang Li; Yijia Sun; Muhammad Zahoor Khan; Yue Yu; Lian Ruan; Li Chen; Juan Zhao; Junchi Jia; Yubao Li; Changfa Wang; Tongtong Wang (Viruses)
Equid herpesvirus type 8 (EqHV-8) is known to cause respiratory disease and miscarriage in horses and donkeys, which is a major problem for the equine farming industry. However, there are currently limited vaccines or drugs available to effectively treat EqHV-8 infection. Therefore, it is crucial to develop new antiviral approaches to prevent potential pandemics caused by EqHV-8. This study evaluates the antiviral and antioxidant effects of cepharanthine against EqHV-8 by employing both in vitro assays and in vivo mouse models to assess its therapeutic efficacy. To assess the effectiveness of cepharanthine against EqHV-8, we conducted experiments using NBL-6 and RK-13 cells. Additionally, we developed a mouse model to validate cepharanthine’s effectiveness against EqHV-8. In our in vitro experiments, we assessed the cepharanthine’s ability to inhibit infection caused by EqHV-8 in NBL-6 and RK-13 cells. Our results demonstrated that cepharanthine has a dose-dependent inhibitory effect, indicating that it possesses anti-EqHV-8 properties at the cellular level. Moreover, we investigated the mechanism through which cepharanthine exerts its protective effects. It was observed that cepharanthine effectively reduces the oxidative stress induced by EqHV-8 by activating the AMPK and Nrf2/HO-1 signaling pathways. Furthermore, when administered to EqHV-8 infected mice, cepharanthine significantly improved lung tissue pathology and reduced oxidative stress. The findings presented herein collectively highlight cepharanthine as a promising candidate for combating EqHV-8 infections.